PENGARUH ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SOUVENIR DI SAUNG ANGKLUNG UDJO - Yulia Rofiati Padminiayu, - (2020)
This study attempted to measure the product atributes on souvenir product purchase decisions in saung anglung udjo. This study applied quantitative approach using non probability sampling technique. In this study, to collecting the data researcher using observation and distributed questionnaire to 100 respondents who had decided to purchase souvenir in Saung Angklung Udjo. Data analysis used in this study is the simple linear regressions. Based on the result of this study, the effect of product attributes on souvenir purchasing decisions at Saung Angklung Udjo is included in the very high category. However, the influence of product attributes is the decision to purchase souvenirs at Saung Angklung Udjo by 23.52% which means weak. Product attributes complete with information needed by visitors are very important in making and improving souvenir purchasing decisions. Accordingly, it is important for managers to improve the quality of the attributes of their souvenir products and services in order to improve souvenir purchasing decisions at Saung Angklung Udjo.